First isolation of Salmonella enterica serovar Soerenga from pregnant sows in Argentina = Primer aislamiento de Salmonella enterica serovar Soerenga a partir de cerdas gestantes en Argentina - Joaquim, Patricia Estefania; Herrera, Mariana; Moroni, Mirian; Chacana, Pablo (Facultad de Ciencias Veterinarias, Universidad Nacional del Nordeste, 2024)
The first isolation of Salmonella enterica serovar Soerenga in Argentina was obtained from stool samples of pregnant sows from intensive production in the province of La Pampa, Argentina, in February 2019. Biochemical identification and serotyping were performed. Moreover, resistance to 17 antimicrobials and presence of 10 virulence genes and pulsed field gel electrophoresis analysis was performed to characterize the isolate, which was resistant to erythromycin, tiamulin and tylosin, and carried the virulence genes sopB, ssaQ, mgtC, avrA and bcfC. Pulsed field electrophoretic profile based on enzymatic digestion of chromosomal DNA with the XbaI enzyme did not coincide with any isolate present in the National Database of the Enterobacteria Lab, INEI ANLIS “Dr. Carlos G. Malbrán” (Buenos Aires, Argentina).